The classroom as privileged space : psychoanalytic paradigms for social justice in pedagogy - Chimbganda, Tapo (Race and education in the twenty-first century., 2017)
This book examines the psychic and emotional effects of the dehumanization of children based on discrimination and difference in classrooms. Using psychoanalysis, it highlights the emotional structures that develop in learners through the repeated trauma of racism and homophobia. Recommended for scholars in education, psychoanalysis, and sociology.